2022
DOI: 10.3390/ijerph19063575
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reciprocal Relationships between Happiness and Life Satisfaction of Working Adults—Evidence from Abu Dhabi

Abstract: This paper examines the relationships between a range of well-being factors and two commonly used subjective well-being measures—happiness and life satisfaction. Data from the second cycle of the Quality of Life (QoL) Survey in Abu Dhabi were used, which included 32,087 working adults. The well-being factors included in the analysis covered various aspects of life themes: income and jobs, work–home balance, health and physical activities, social and community services, living environment, and family/friends’ r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 66 publications
(105 reference statements)
1
7
0
Order By: Relevance
“…The results indicate that the indirect effect between job satisfaction and depressive symptoms among Chinese adults aged 35-60 years can be mediated by subjective well-being and life satisfaction, respectively. Consistent with other research findings [81], higher job satisfaction contributes to the development of personal identity and enables people to participate in social communication with a healthy frame of mind [37]. In other words, the individuals' positive evaluation of their actual work status makes them more likely to catch the gorgeous moments in life and increases their subjective well-being, which in turn positively influences mental performance and provides individuals with protection from depression [41].…”
Section: The Mediation Effect Of Subjective Well-being and Life Satis...supporting
confidence: 75%
“…The results indicate that the indirect effect between job satisfaction and depressive symptoms among Chinese adults aged 35-60 years can be mediated by subjective well-being and life satisfaction, respectively. Consistent with other research findings [81], higher job satisfaction contributes to the development of personal identity and enables people to participate in social communication with a healthy frame of mind [37]. In other words, the individuals' positive evaluation of their actual work status makes them more likely to catch the gorgeous moments in life and increases their subjective well-being, which in turn positively influences mental performance and provides individuals with protection from depression [41].…”
Section: The Mediation Effect Of Subjective Well-being and Life Satis...supporting
confidence: 75%
“…Another promising direction would involve a cross-cultural perspective. 51 By contrasting the Chinese work environment with other cultural backgrounds, 52–54 we could better discern the universality or specificity of our findings. 55 This comparative approach might reveal the extent to which cultural values shape the dynamics of life satisfaction among aged workers.…”
Section: Discussionmentioning
confidence: 92%
“…Yet, in the present study we found that this decline was larger among females, national students, students of higher SES and in British schools, as well as in the emirates of Sharjah, Abu Dhabi, RAK and Dubai. This may be explained by rising mental health issues, which serve to drag OLS scores downward (Badri et al, 2022 ; Lombardo et al, 2018 ). Declines in youth wellbeing have been especially pronounced in countries that are more egalitarian, with higher GDP per capita, and where concurrent increases in academic pressure are observed (Borgonovi & Han, 2021 ; Cosma et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%